ANTI-CORRUPTION EDUCATION AT TECHNICAL UNIVERSITY - Oleksiy Kravchuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
The article considers the main activities of a modern technical university in the field of anti-corruption education targeted at the development of the generic competencies in future professionals. The article is based on the author's observations gained during his work at the National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute" as an anti-corruption officer of the University, department head and professor. The main activities of modern technical university in the abovementioned field should aim at introducing anti-corruption topics or subtopics into the courses; offering special optional courses; elaboration of anti-corruption programme of the university and its implementation; ensuring anti-corruption training of the personnel; including issues on preventing and combating corruption in the advanced training programmes for public servants; adherence of teaching staff and university administration to high standards of professional ethics. The author proposes topics and subtopics to be included in the curricula for students in different specialisations and into training programmes for postgraduate education. University graduates should be motivated, skilful professionals with a formed proficient mental attitude with regard to the aversion of corruption.